In vitro biofilms and antifungal susceptibility of dermatophyte and non‐dermatophyte moulds involved in foot mycosis. Issue 2 (15th October 2017) - Toukabri, Nourchéne; Corpologno, Serena; Bougnoux, Marie‐Elisabeth; El Euch, Dalenda; Sadfi‐Zouaoui, Najla; Simonetti, Giovanna
Summary: Tinea pedis and onychomycosis are among the commonest fungal diseases in the world. Dermatophytes and, less frequently, non‐dermatophyte moulds are aetiological agents of foot mycosis and are capable of forming biofilms. Fungal biofilm has demonstrated increasing drug resistance. This work aims to evaluate, in vitro, the ability to form biofilm and the susceptibility to antifungal drugs of sessile dermatophytes and non‐dermatophyte moulds involved in foot mycosis. Thirty‐six dermatophytes and non‐dermatophyte moulds isolated from Tunisian patients with foot mycoses, and identified with MALDI‐TOF have been tested. MICs of fluconazole, econazole, itraconazole, terbinafine and griseofulvin were carried out using CLSI broth microdilution method. The ability to form biofilm and antifungal activities of drugs against fungal biofilm formation has been quantified by Crystal Violet and Safranin Red staining. Biomass quantification revealed that all species studied were able to form biofilms in vitro after 72 hours. Fluconazole, econazole, itraconazole and terbinafine inhibited fungal growth with MIC values ranging from 0.031 to >64 μg mL −1 . The best antifungal activity has been obtained with terbinafine against Fusarium solani . Econazole showed the highest activity against fungal biofilm formation. These findings can help clinicians to develop the appropriate therapy of foot mycosis.